Building a Culture of Tolerance Through Sustainable Leadership, Cultural Intelligence, and Social Adaptation: Evidence from a Multicultural Community in Indonesia - Neni Alyani; Lilis Rosita; M. Miftahul Madya (UIN Sunan Gunung Djati, 2025)
This study aims to analyze the mechanisms through which a culture of tolerance emerges in multicultural communities by examining three key factors: sustainable leadership (SL), cultural intelligence (CQ), and social adaptation (AD). This focus is crucial because tolerance is often understood as a product of state policy, whereas empirical evidence consistently shows that tolerant practices are primarily constructed through grassroots leadership and everyday social interactions. Methodologically, this research employs a quantitative approach, collecting survey data through Google Forms from residents of Gang Luna, Bandung, West Java, and analyzing the data using Partial Least Squares–Structural Equation Modeling (PLS–SEM). The outer model was evaluated through tests of convergent validity, discriminant validity, internal reliability, and multicollinearity, while the inner model was assessed using R², Q², path coefficients, effect size, and significance testing with 5000 bootstrapped subsamples. The findings reveal three major results. First, sustainable leadership has a positive and significant effect on cultural intelligence, indicating that dialogic and inclusive leadership at the community level strengthens residents’ cultural readiness in navigating differences. Second, cultural intelligence significantly enhances social adaptation, as individuals with higher CQ demonstrate stronger abilities to adjust, recognize cultural sensitivities, and maintain intergroup harmony. Third, SL, CQ, and AD jointly shape a stable and sustainable culture of tolerance. The mediating effects of CQ and AD show that tolerance is not merely the outcome of formal policy but is produced through social learning, difference management, and everyday cross-identity interaction. The study’s implications highlight the importance of strengthening community leadership capacity, expanding intercultural literacy programs, and reformulating tolerance policies to be more responsive to the lived social dynamics of residents. In terms of originality, this research offers an empirical model that explains the pathways of tolerance formation grounded in everyday multiculturalism and community-driven leadership—an area that remains underexplored in Indonesian tolerance studies.